Determinants of Export Volume in Indonesia’s Textile and Textile Products Industry: An Analysis Using the Gravity Model - Saputra, Clara Elisabeth Jahja; Budiningsih, Ni Ketut (Business and Investment Review, 2025)
Indonesia’s textile and textile products (TTP) industry plays a vital role in the national economy, contributing significantly to employment and foreign exchange. However, since 2016, the export volume of TTP has declined, raising concerns about competitiveness and structural resilience. This study investigates the macroeconomic determinants of Indonesia’s TTP export volume to five major trading partners—United States, Japan, South Korea, China, and Germany—over the period 2014–2023. Using the gravity model framework, the analysis incorporates five explanatory variables: GDP per capita, geographical distance, trade openness index, real exchange rate, and population growth rate. Panel data regression is applied, with the Common Effect Model (CEM) selected based on diagnostic tests. The results show that GDP per capita, real exchange rate, and population growth rate positively and significantly affect export volume, while geographical distance and trade openness index exert a negative and significant influence. These findings confirm the relevance of the gravity model in explaining bilateral trade flows and highlight the importance of purchasing power, exchange rate stability, and demographic expansion in driving exports. Conversely, logistical barriers and intensified competition in liberalized markets may suppress export performance. The study offers policy insights for enhancing Indonesia’s export strategy through market diversification, improved logistics, and industrial competitiveness.